Measurements of W and Z/γ∗ cross sections and their ratios in p+p collisions at RHIC - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review, 2021)
We report on the W and Z/γ∗ differential and total cross sections as well as the W+/W− and (WW−)/(Z/γ∗) cross section ratios measured by the STAR experiment at RHIC in p+p collisions at √s=500 GeV and 510 GeV. The cross sections and their ratios are sensitive to quark and antiquark parton distribution functions. In particular, at leading order, the W cross section ratio is sensitive to the ¯d/¯u ratio. These measurements were taken at high Q2∼M2W,M2Z and can serve as input into global analyses to provide constraints on the sea quark distributions. The results presented here combine three STAR datasets from 2011, 2012, and 2013, accumulating an integrated luminosity of 350 pb−1. We also assess the expected impact that our W+/W− cross section ratios will have on various quark distributions, and find sensitivity to the ¯u−¯d and ¯d/¯u distributions.
Gesehen am 18.02.2021
Im Titel ist der griechische Buchstabe "ast" als Tropfensternchen (englisch: teardrop-spoked asterisk) dargestellt